Framing Communication Messages to Promote Covid-19 Protective Behaviors in Mexico: An Application of Protection Motivation Theory - Arroyo López, Pilar Ester; Cárcamo Solís, María de Lourdes (Journal of Behavior, Health & Social Issues, 2021)
The objective of this research was to explore which elements of the Protection Motivation Theory (PMT) influence the intentions to reinforce the COVID-19 protective behaviors to frame communication messages that promote the voluntary adoption of health-protective practices. An experimental study was conducted by testing all combinations of the four PMT components at two levels, low and high. To take into account the age of participants, four age groups were considered. Eight combinations of the factorial experiment were evaluated by individuals of each age group. Additionally, the effect of the individual social responsibility and medical condition of participants, and the contagion risk of the region of residence were considered. Several statistical analyses were applied to the experimental data collected at two regions, high contagion risk and medium contagion risk. The results of the analysis indicate the threat and appraisal components of the PMT do not act independently but interactively. If the severity is tolerable, increasing vulnerability rises the intentions to reinforce the COVID-19 protective practices among residents of both regions. While in the case of the high contagion risk region, vulnerability dominates the intentions to strengthen protective behaviors when self-efficacy is high. But if vulnerability perceptions are low, then an improvement in self-efficacy enhances the intentions to reinforcing protection. According to these findings, communication messages that simultaneously highlight severity and vulnerability result in negative fear emotions and low perceived control that demotivate individuals to strengthen their protective behaviors to prevent the spread of COVID-19.